Políticas de inserção de alunos no mercado de trabalho sob a ótica das instituições de ensino superior de tecnologia - Lima, Débora Andrade (2015)
This work aims to analyze inclusive policies for students in labor market under the view of institutions of higher education on technology. This research also intends to know the challenges of inclusion of a student in the labor market by these institutions, as well as their relation with the public policies, and the possibilities of increasing the numbers of that inclusion. Through documental and bibliographic research and the use of deep interviews with coordinators and directors, a case study with two higher education institutions was accomplished: Instituição Federal de Educação, Ciência e Tecnologia do Ceará (IFCE) and Universidade Estadual Vale do Acaraú (UVA). It has been shown, with this research, that institutional policies in inclusion of students in labor market are related to receiving of demands and disclosure of internships and jobs offered for partner companies and integration agents, beyond the concern on forming a professional citizen, following-up the internships so the student can attend them or work in his actuation area, not becoming cheap workforce; that the existent relations between market/government referring to actions in inclusion in labor market happen in the moment of the offering of opportunities in public and private institutions and integration agents and in encounters promoted by these integration agents, as CIEE and IEL; that processes referent to inclusion of more prominent students in labor market could be about the receiving of opportunity offers, their analysis and disclosure, beyond the in loco follow-up of part of the trainees, career orientation and opportunities for complementary activities, so knowledge can be extended and, consequently, make inclusion easier, in an enabling economic context; and that the perception of executives in relation to the inclusion of students in labor market increases year by year, but that students need to get even more involved in the complementary activities to increase their possibilities of inclusion. A virtuous circle was observed, in the sense that there must be public policies which promote the economic growth of the nation and, thus, the increasing for trainees and qualified workers demand, added to public policies for expansion on technological education; among them, investments which promote a high level quality of education, so that good trainees and workers can be absorbed by label market.